Deconstructive criticism of De Saussure's linguistic sign theory (مجلة إحالات, 2026)
The purpose of this search is , to explore the causes and backgrounds which isbehind the downsizing of linguistic traditions, and the Western semantic of the role ofwriting, it considers it just a secondary residual, and an external physical technique torepresent speech. In exchange for the absolute presence that the voice achieves, through thevitality of the pronouncement and its precedence, the visual, dimensional, writing embodiedon a tangible surface eligible for this, just trying to regain that presence, with imperfect,distorted, and dangerous restoration, and dangerous according to these metaphysicalbackgrounds centered on logos, sound, and the philosophy of presence. And this is an ancientepistemological and linguistic tradition that continues today, as it will be an epistemicreference for the establishment of the sciences of language and linguistics, since Aristotlewho saw that the sound is closer to the meaning, passing by Plato, which warned againstwriting, accusing it of encouraging laziness, arrival to De Saussure, who made sound a basisfor the theory of sign and meaning.